Autologous Fat Transfer in a Patient with Lupus Erythematosus Profundus - Jimi Yoon; Hwa Mi Kim; Tae-Heung Kim; Chung-Won Kim; Young-Woo Sun; Tae-Jin Yoon (Karger Publishers, 2012)
Lupus erythematosus profundus, a form of chronic cutaneous lupus erythematosus, is a rare inflammatory disease involving in the lower dermis and subcutaneous tissues. It primarily affects the head, proximal upper arms, trunk, thighs, and presents as firm nodules, 1 to 3 cm in diameter. The overlying skin often becomes attached to the subcutaneous nodules and is drawn inward to produce deep, saucerized depressions. We present a rare case of lupus erythematosus profundus treated with autologous fat transfer.